Integritas Akademik Mahasiswa berhubungan dengan Kemampuan dalam Mengatur Belajar Secara Mandiri - Muhammad Nur Akmal Hidayat; Made Sumarwati; Wastu Adi Mulyono (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2020)
Background. Academic disintegration behavior is still common. Academic integrity (AI) is the consistent behavior of students in upholding the values of honesty, trust, fairness, respect, and responsibility during the learning process. Self regulated learning (SRL) is the ability of students in using independence strategies, setting and controlling their learning goals. This study aims to determine the relationship between SRL and AI in Unsoed Faculty of Health Sciences Nursing Department students.Method. This research used quantitative study with the cross sectional design. The sampling technique used total sampling technique. The sample size was 136 respondents. The research instrument used a questionnaire and the data were analyzed using the correlation Pearson test.Results.The results of the study showed that the majority of respondents were female (93.4%) and less student live with parents (21.3%). The average score of SRL and AI values is relatively high. A Pearson correlation showed there was a weak, positive correlation between SRL and AI which was statistically significant in nursing students of Health Sciences Faculty (r = 0.399; p < 0.001).Conclusion. A better self regulated learning is associated with a better academic integrity.